Bingo capitalism the law and political economy of everyday gambling - Bedford, Kate 1975- (Oxford New York, NY Oxford University Press, 2019)
Casinos are often used by political economists, and popular commentators, to think critically about capitalism. Bingo - an equal chance numbers game played in many parts of the world - is overlooked in these conversations about gambling and political economy. Bingo Capitalism challenges that omission by asking what bingo in England and Wales can teach us about capitalism and the regulation of everyday gambling economies. The book draws on official records of parliamentary debate, case law, regulations and in-depth interviews with both bingo players and workers to offer the first socio-legal account of this globally significant and immensely popular pastime. It explores the legal and political history of bingo and how gender shapes, and is shaped by, diverse state rules on gambling. It also sheds light on the regulation of workers, players, products, places, and technologies. In so doing it adds a vital new dimension to accounts of UK gambling law and regulation.through Bingo Capitalism, Bedford makes a key theoretical contribution to our understanding of the relationship between gambling and political economy, showing the role of the state in supporting and then eclipsing environments where gambling played a key role as mutual aid. In centering the regulatory entanglement between vernacular play forms, self-organized membership activity, and corporate leisure experiences, she offers a fresh vision of gambling law from the everyday perspective of bingo.
Introduction -- Conclusion Bingo as practice and lens -- Eyes down : early state attention to bingo (1900-68) -- Maggie's den : commercial deregulation, charity and adapted gambling moralities (1968-97) -- "Something rather perverse" : gambling reform and the sidelining of bingo under New Labour (1997-2005) -- Death of the ex-policeman : gender, class, and personnel licensing in the era of self-regulation -- The sociological significance of membership : snowballs, strangers, virgins, and regulars -- State optics and bingo definitions : bringing workers back into the regulation of technologies, mechanics, and places of play -- Innovation framing, regulation, and user adaptation online : why there are no flasks in online bingo -- Social responsibility, new technologies, and problem gambling in bingo : where to point the dabber? -- From lines and corners to the full house.
Includes bibliographical references (pages 323-353) and index.
Keywords: Bingo -- Economic aspects -- England; Bingo -- Economic aspects -- Wales; Bingo -- Law and legislation -- England; Bingo -- Law and legislation -- Wales; Gambling -- Electronic books -- Law and legislation -- Great Britain